Implementasi Projek Penguatan Profil Pelajar Pancasila Pada Dimensi Gotong Royong dalam Kurikulum Merdeka - Nai Rahmawati; Asep Tutun Usman; Ja’far Amirudin; Ani Siti Anisah (PT PUBLIKASI INSPIRASI INDONESIA, 2026)
This research is motivated by the existence of the mutual cooperation dimension, which is an important component in improving student attitude education in schools. Judging from how students participate in various activities, especially in the project to strengthen the profile of Pancasila students, it is seen that there are students who are active in P5, but also students who are less active, such as in making products from used goods, and students who are not comfortable with their own groups. The purpose of the study is to describe the implementation of the project to strengthen the profile of Pancasila students (P5) in the mutual cooperation dimension at Madrasah Ibtidaiyah Negeri 4 Cinisti Garut, for fourth grade students. Describe the development of the mutual cooperation dimension in the implementation of the project to strengthen the profile of Pancasila students for fourth grade students. Describe the inhibiting factors in the development of mutual cooperation attitudes in the implementation of the project to strengthen the profile of Pancasila students for fourth grade students. Describe the solutions sought to overcome obstacles in the implementation of the mutual cooperation dimension in the project to strengthen the profile of Pancasila students for fourth grade students. This study used a qualitative descriptive method with data collection techniques consisting of observation, interviews, and documents. The results indicate that the Pancasila Student Profile Strengthening Project in the Mutual Cooperation Dimension within the Independent Curriculum at Madrasah Ibtidaiyah Negeri 4 Cinisti Garut has successfully fostered a spirit of mutual cooperation among students, especially in fourth grade. However, there were obstacles in project implementation; some groups encountered difficulties working in groups. Therefore, the teacher helped students understand and reflect on their work.